Pengembangan Sistem Informasi Presensi Kehadiran Guru Menggunakan Model Sequential Linier - Wahju Tjahjo Saputro; Ike Yunia Pasa; Wuri Setyowardani (Universitas Muhammadiyah Purworejo, 2021)
The manual attendance system currently running at SMK TKM Teknik Purworejo has not been able to produce fast and accurate data so it is not easy to monitor teacher attendance. Therefore, a computerized Teacher Presence System is needed to produce faster and more accurate data at SMK TKM Teknik Purworejo. In making the Presence Information System for Teacher Attendance at SMK TKM Teknik Purworejo the Sequential Linear or Classic Life Cycle Model or commonly referred to as the Waterfall model is used. Linear Sequential is an approach to systematic and sequential software development that starts at the system level and progresses throughout the analysis, design, code, and testing. The data collection procedure was carried out to collect the data needed in the study, in this case using the methods of observation, interviews, and documentation. The system built can provide various facilities such as the process of adding, changing, and deleting admin data, teacher data, permission type data. It also presents the process of updating general and school settings. There is also a facility to make an entry and exit presence, which is equipped with a photo of the presence and checking the IP connection used. And also displays attendance and permission reports.